2020
DOI: 10.1155/2020/4690713
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Tears Oxidative Stress Status and Sleep Disturbances in Irritable Bowel Syndrome Patients

Abstract: According to the latest gastrointestinal disorders diagnostic criteria (ROME IV), the irritable bowel syndrome (IBS) is mainly characterized by the presence of abdominal pain and changes in intestinal transit. However, both sleep impairments and oxidative status changes (in patients’ sera, mucosal level, and other body fluids) were reported IBS. Thus, in this study, we aimed to evaluate several aspects regarding the oxidative stress status in patients’ tears as well as sleep disturbances by comparison with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Our findings of an association between shorter sleeping duration and IBS are supported by one study [23], in contrast to another [22]. The association between sleeping onset difficulties and IBS remained in the full model, in alignment with other studies which describe this phenomenon as a dominant symptom [14,[23][24][25]. Interestingly, most of the IBS patients related their sleeping disturbances to non-IBS symptoms, such as nocturia, back pain, headache, and arthralgias [22], which complicates the research field further.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings of an association between shorter sleeping duration and IBS are supported by one study [23], in contrast to another [22]. The association between sleeping onset difficulties and IBS remained in the full model, in alignment with other studies which describe this phenomenon as a dominant symptom [14,[23][24][25]. Interestingly, most of the IBS patients related their sleeping disturbances to non-IBS symptoms, such as nocturia, back pain, headache, and arthralgias [22], which complicates the research field further.…”
Section: Discussionsupporting
confidence: 88%
“…Sleeping deprivation has been shown to lead to enhancements of nociception and a diminished capacity to regulate emotional reactivity leading to depression and/or anxiety [ 29 ], and it affects the autonomous nervous system and HPA axis in similarity to chronic stress, leading to visceral hypersensitivity [ 11 , 30 ]. Furthermore, biomarkers for oxidative stress in tears correlated with GI symptoms in IBS patients with sleeping disorders [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cuba traditional medicine, it has been used for gastro-intestinal pains, rheumatism, and kidney diseases [ 19 ]. More recently, CA was reported for its action against irritable bowel syndrome [ 21 ] and for its hepatoprotective properties (mainly evidenced against ethylic alcohol and CCl 4 ), lipid lowering actions, and its positive effects against vascular diseases by promoting blood microcirculation [ 18 , 19 , 20 , 22 , 23 , 24 , 25 ]. The pharmacological properties of CA are generally attributed to saponosides (such as chrysanthellins A and B) and flavonoids compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58] According to previous literature, a higher oxidative or inflammatory condition in patients is strongly associated with poor sleep quality and sleep disturbance problems. 59,60 Spirulina bioactive components, including phycobiliprotein, β-carotene and phycocyanin, can elicit decreases in lipid peroxidation or attenuate expression of inflammatory genes, which can ameliorate oxidative or inflammatory status, [56][57][58] and consequently enhance sleep quality. Third, spirulina can increase leptin secretion from adipose tissue 61 ; indeed, Hirota et al 62 suggested that plasma leptin concentrations were positively related to higher sleep quality.…”
Section: Ta B L Ementioning
confidence: 99%